2016
DOI: 10.7554/elife.16955
|View full text |Cite
|
Sign up to set email alerts
|

mRNA poly(A)-tail changes specified by deadenylation broadly reshape translation in Drosophila oocytes and early embryos

Abstract: Because maturing oocytes and early embryos lack appreciable transcription, posttranscriptional regulatory processes control their development. To better understand this control, we profiled translational efficiencies and poly(A)-tail lengths throughout Drosophila oocyte maturation and early embryonic development. The correspondence between translational-efficiency changes and tail-length changes indicated that tail-length changes broadly regulate translation until gastrulation, when this coupling disappears. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
210
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(238 citation statements)
references
References 54 publications
21
210
3
Order By: Relevance
“…3 ′ UTRs are common targets of RBPs and miRNAs that regulate mRNA stability and translation (Matoulkova et al 2012). In transcriptionally silent embryos, maternal mRNA translation is tightly controlled by regulation of poly(A) tail length, whereas mRNA stabilities remain largely unaffected (Subtelny et al 2014;Eichhorn et al 2016). Analysis of available ribosome and poly(A) tail profiling data (Lee et al 2013;Subtelny et al 2014) revealed that Hnrnpa1 targets harbor significantly longer poly(A) tails (median length: 34.4 and 28.1, P = 7 × 10 −60 ) and display higher TE than nonbound mRNA counterparts (median TE: 0.94 and 0.53, P = 5.02 × 10…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 ′ UTRs are common targets of RBPs and miRNAs that regulate mRNA stability and translation (Matoulkova et al 2012). In transcriptionally silent embryos, maternal mRNA translation is tightly controlled by regulation of poly(A) tail length, whereas mRNA stabilities remain largely unaffected (Subtelny et al 2014;Eichhorn et al 2016). Analysis of available ribosome and poly(A) tail profiling data (Lee et al 2013;Subtelny et al 2014) revealed that Hnrnpa1 targets harbor significantly longer poly(A) tails (median length: 34.4 and 28.1, P = 7 × 10 −60 ) and display higher TE than nonbound mRNA counterparts (median TE: 0.94 and 0.53, P = 5.02 × 10…”
Section: Resultsmentioning
confidence: 99%
“…Third, we show that the mutation of the AGGGA hexanucleotide Hnrnpa1 binding motif in the 3 ′ UTR of an Hnrnpa1 target decreases Hnrnpa1 binding, shortens the poly(A) tail, and decreases translational output of a eGFP reporter. It has been proposed that selective deadenylation of maternal mRNAs is likely a major determinant of the differences in poly(A) tail length and TE between maternal transcripts in fly embryos, whereas CPE-mediated cytoplasmic polyadenylation creates these differences in vertebrates (Eichhorn et al 2016). Thus, Hnrnpa1 likely protects transcripts from active deadenylation or promotes their polyadenylation in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations